The living street an urban art and lifestyle hub - Rodriguez, Janina Q. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
Physical inactivity has increased due to too much working hours as well as convenience brought about by different technologies. An active lifestyle through sports or exercise greatly impacts an individual’s wellness by fulfilling his or her physical, social, intellectual and emotional needs.
The premise of the study is to promote an active lifestyle and enable different forms of expression through the integration of urban and lifestyle sports. The urban planning concept of the “living street” is used in both indoor and outdoor spaces to create a deliberate social space as it enables interaction between enthusiasts and non-enthusiasts alike. Consequently, this consciousness in the environment prompts motion and adaptability generating a safer place for play.
The integration of different types of users and activities established the need for a multifunctional facility that will act as a massive exhibit hall for movement –for the expression of both mind and the body hence, The Street.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Sports & Recreation